Improving patient safety and access to healthcare: The role of pharmacist-managed clinics in optimizing therapeutic outcomes - Shabeer Ali Thorakkattil; Sainul Abideen Parakkal; K.T. Mohammed Salim; Savera Arain; Gopika Krishnan; Hafees Madathil; Ajmal Karumbaru Kuzhiyil; Ammad Aslam; Suhaj Abdulsalim; Mahmathi Karuppannan; Sathvik Belagodu Sridhar; Javedh Shareef; et al. (Elsevier, 2024)
Contemporary patient care requires a multidisciplinary approach to monitoring, assessing, and managing diseases. Promoting multidisciplinary approaches encourages the purposeful participation of many healthcare professionals and harnessing their combined knowledge to provide tailored treatment plans. Pharmacists, skilled and knowledgeable professionals in medication management, drug-related problems, and disease prevention, can offer vital interventions that contribute to improved patient outcomes. Advances in healthcare and information technology have expanded pharmacists' professional roles and made them essential in healthcare. Pharmacist-managed clinics (PMCs), an innovative healthcare approach, could potentially improve patient safety, satisfaction, accessibility, and affordability to quality healthcare. Spread across the healthcare continuum, pharmacists have a well-defined role in providing comprehensive pharmaceutical care and interprofessional collaboration, further reinforcing the necessity of establishing PMCs. This narrative review aims to compile and summarize information on PMCs from PubMed, Scopus, Web of Science, and Google Scholar till December 2023. The PMC shortlist covers specialties such as cardiovascular, hematologic, endocrine, pain medicine, respiratory medicine, infectious diseases, gastrointestinal, nephrology, neurology, and oncology. Pharmacists in disease-specific PMCs have demonstrated improved treatment outcomes and access to specialty care. Additionally, based on peer-reviewed literature, the review also highlights how PMCs enhance the pharmacist's role in improving disease-specific outcomes, overall quality of care, and medication management. The inclusion criteria are randomized controlled trials, case-control studies, cohort studies, and pre-post studies involving patients from cardiology, hematology, endocrinology, pain medicine, respiratory medicine, infectious diseases, neurology, nephrology, gastroenterology, and oncology specialties, focusing on pharmacist-driven clinics, published in English, and covering any geographical location. The exclusion criteria include review articles, proposed models, commentaries, editorials, and those published in languages other than English. Our findings reveal that PMCs are underutilized globally. PMCs work better in developed countries, possibly on account of robust healthcare infrastructure, adequate healthcare budgets, availability of trained pharmacists, and supportive regulatory environments. The review found that pharmacist-led interventions, such as medication monitoring and patient education, significantly enhance therapeutic outcomes. Pharmacist Managed Clinics improve affordability and acceptability, expanding healthcare access in outpatient and inpatient settings. This review also highlights the critical need for implementing PMCs to improve healthcare delivery, particularly in providing comprehensive and accessible services in developing countries.